2018
DOI: 10.1021/acssuschemeng.7b03154
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Sweet Sorghum Juice for the Production of Astaxanthin as a Biorefinery Co-Product by Phaffia rhodozyma

Abstract: This work investigates cultivating the red-pigmented yeast Phaffia rhodozyma in sweet sorghum juice (SSJ) to assess the production of astaxanthin as a potential biorefinery co-product. Shake flask cultures on defined sugar medium indicated that all three sugars (sucrose, glucose, and fructose) could be consumed with adequate nitrogen and nutrient supplementation. Only modest biomass growth and astaxanthin production could be achieved in SSJ without nitrogen supplementation; however, combining nitrogen suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…The samples were separated on a Bio-Rad (Hercules, CA, USA) Aminex HPX-87H column equipped with a cation H + guard column. The operation conditions of the HPLC have been previously reported [24,25]. The astaxanthin was extracted from the cells using acetone according to previous methods [24].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The samples were separated on a Bio-Rad (Hercules, CA, USA) Aminex HPX-87H column equipped with a cation H + guard column. The operation conditions of the HPLC have been previously reported [24,25]. The astaxanthin was extracted from the cells using acetone according to previous methods [24].…”
Section: Methodsmentioning
confidence: 99%
“…The operation conditions of the HPLC have been previously reported [24,25]. The astaxanthin was extracted from the cells using acetone according to previous methods [24]. A 1 mL aliquot of fermentation broth was mixed with 3 mL of water in a glass test tube.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The C/N ratio has a significant influence on cell growth and carotenoid biosynthesis. In other studies, was related that a high C/N ratio increased the carotenoid production yield due to the nitrogen limitation [22,23].…”
Section: Discussionmentioning
confidence: 90%
“…As a C4 crop, sweet sorghum contains rich fermentable sugars in its stems (such as sucrose, glucose and fructose) and a variety of cultivars and growing characteristics such as high biomass yield and rapid growth, which make it an attractive feedstock for value-added biochemical production. A number of fuels and bio-chemicals have been successfully produced using sweet sorghum juice (SSJ) as feedstocks [7][8][9][10][11][12]. In a previous study, we have shown that SSJ was the preferred feedstock for enduracidin production with approximately equivalent e ciency to that of glucose, and S. fungicidicus M30 can also produce 1.01 ± 0.05 g/L of enduracidin via clari cated SSJ and fed-batch strategy [13].…”
Section: Introductionmentioning
confidence: 99%